Acceptability of a perturbation-based balance training programme for falls prevention in older adults: a qualitative study. Issue 2 (24th February 2022) - Gerards, Marissa H G; Sieben, Judith; Marcellis, Rik; de Bie, Rob A; Meijer, Kenneth; Lenssen, Antoine F
Abstract : Introduction: Perturbation-based balance training (PBT) is reported to effectively reduce falls in older adults and may even be superior compared with various exercise programmes. Due to the nature of the intervention, requiring unpredictable balance perturbations, the question arises whether acceptability is an issue in PBT. Objective: To evaluate the acceptability of PBT in older adults with a recent history of falls. Design, method, participants and setting: This is a qualitative study in which semistructured interviews were conducted in 16 older adults (14 women and 2 men, mean age 73.6±6.0 years) who completed a three-session PBT protocol as part of another study in a university medical centre in the Netherlands. Typical case and purposive sampling strategies were applied. Interviews were based on the theoretical framework of acceptability (TFA) alongside context-specific factors and analysed using a template analysis approach. Results: The results indicate that this PBT protocol is perceived as acceptable by older adults with a recent history of falls and highlight key areas for potential future modifications. Enjoyment of the novel training and technology, being able to feel safe during training, and perceived impact of increased self-efficacy and balance confidence were identified as facilitating factors. Potential issues included initial apprehension or anxiety during training and perceived impact being predominantly psychological instead of physical. Complementary to the TFA one additional theme emerged which described challenges regarding the training setting, such as preference for group training in some participants and travel to the training location. Conclusions: The results suggest that PBT is perceived acceptable by older adults with a history of falls. Increasing the social aspect of training and sharing the experiences of peers may be considered to enhance acceptability to new participants who initially feel apprehensive or anxious about their ability to participate in future implementation of PBT. Trial registration number: The article is linked to a randomised clinical trial registered on https://www.trialregister.nl/trial/7680, NL7680; Results.